(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Retained placenta is considered as one of the important causes of postpartum hemorrhage (primary and secondary). It may lead to complications such as renal failure and shock. Objective: To determine the occurrence of acute renal failure and hypovolemic shock in patients of retained placenta. Outcome measure: Frequency of ARF and hypovolemic shock. Study design: Cross sectional study. Setting: Department of Obstetrics and Gynecology Shaikh Zaid Women Hospital Larkana Subjects: Patients with age group (18-40 years) admitted in labor room were included. Women with renal stone or infections, receiving nephrotoxic drugs and pre-eclampsia were excluded. Methods: Patients meeting the inclusion criteria will be included after written informed consent. A detailed history and examination were done. Patients were labeled as suffering from hypovolemic shock, if they have pulse rate >100 and systolic BP<100mmHg in presence of any one Cold peripheries, Decrease capillary retiling (<3 sec). Patients were suffering from ARF, if she has loss of renal function i.e., elevated (about baseline which is 10-40 mg/dl) and creatinine (about baseline which is 0.4-1.6 mg/dl) along with oliguria (i.e., 24hrs U.O.P <400ml). The analysis of data was done with the use of SPSS version 10. Results: The mean age of included participants is 29.8±5 years. From 307 patients, primiparity accounted for 117 (38%), parity 2-3 for 135 (44%) and parity 4-5 for 55 (18%) cases. The systolic blood pressure of 145 (47.2%) patients was <100 mmHg and in 162 (52.8%) patients was >100 mmHg. A total of 299 (97.4%) patients has urine output of >400 ml in 24 hours and 8 (2.6%) cases have urine output of <400 ml in 24 hours. Of 307 patients 10 (3.2%) had acute renal failure and 69 (22.5%) had shock. Conclusions: From this study, it was observed that the frequency of ARF and hypovolemic shock is high in patients with retained placenta.